The symbolic meaning of the Akkatere tradition for the indigenous people of the Kajang community - Mandjarreki, Sakaruddin; Syam, Lukman; Andriyani, Riska (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2023)
This research aims to describe the empirical reality surrounding the implementation of unique traditions. Unique because Akkatere (cutting hair) is claimed as a ritual activity that is aligned with the implementation of the pilgrimage. All individuals or families who have performed Akkatere are considered to have performed the pilgrimage. This research is qualitative with a phenomenological approach. Data sources include village heads, traditional leaders, and community leaders who understand this tradition. Methods of data collection include observation, interviews, and documentation. Data analysis techniques are carried out through data reduction, data presentation, and drawing conclusions. The results of the study show that the Akkattere tradition is carried out by individuals who are economically capable, of traditional descent, and still obedient to the tide. The implementation process begins with apparungrungi and ends with the distribution of dallekang. The meaning of the Akkattere tradition includes; rituals of worshiping God, respecting ancestors, respecting customs, strengthening ties of friendship, and giving alms.